2001
DOI: 10.1021/om000845j
|View full text |Cite
|
Sign up to set email alerts
|

Solution and Nujol Matrix Photochemistry of (η5-C5H5)2Os2(CO)4 and Nujol Matrix Photochemistry of (η5-C5H4CH3)2Ru2(CO)4 and (η5-C5H5)M(CO)2H, Where M = Ru and Os

Abstract: Lowering the temperature of a Nujol solution of (η 5 -C 5 H 4 CH 3 ) 2 Ru 2 (CO) 4 containing bands of the trans-and cis-bridging and trans-nonbridging isomers from room temperature to ca. 90 K results in complete disappearance of the bands of the trans-terminal isomer. The photochemistry of (η 5 -C 5 H 4 CH 3 ) 2 Ru 2 (CO) 4 in frozen Nujol at 90 K differs subtly from that of (η 5 -C 5 H 5 ) 2 Ru 2 (CO) 4 in inert gas matrixes at 12 K in that the trans-bridging isomer is found to undergo photolysis at high en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
19
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 35 publications
7
19
0
Order By: Relevance
“…Interestingly, the dicarbonyl analogue RuHCl­(CO) 2 (PPh 3 ) 2 did not show any photoinduced ligand-elimination reaction but underwent reversible photoisomerization according to UV and IR spectra . Irradiation of CpRuH­(CO) 2 in frozen nujol yielded [CpRuH­(CO)], again displaying CO photodissociation . Surprisingly, it was observed that triethylsilane reductive elimination competes with CO photorelease in RuH­(SiEt 3 )­(CO) 3 (PPh 3 ), for which the authors postulated an excited state similar to that of Ru–H 2 species due to the parallel to the corresponding oxidative addition reaction.…”
Section: Metal Hydride Photochemistry By Transition Metal Groupmentioning
confidence: 57%
See 2 more Smart Citations
“…Interestingly, the dicarbonyl analogue RuHCl­(CO) 2 (PPh 3 ) 2 did not show any photoinduced ligand-elimination reaction but underwent reversible photoisomerization according to UV and IR spectra . Irradiation of CpRuH­(CO) 2 in frozen nujol yielded [CpRuH­(CO)], again displaying CO photodissociation . Surprisingly, it was observed that triethylsilane reductive elimination competes with CO photorelease in RuH­(SiEt 3 )­(CO) 3 (PPh 3 ), for which the authors postulated an excited state similar to that of Ru–H 2 species due to the parallel to the corresponding oxidative addition reaction.…”
Section: Metal Hydride Photochemistry By Transition Metal Groupmentioning
confidence: 57%
“…If the temperature is lowered to 4 K, however, pure H 2 can be condensed successfully . Several studies of metal hydride complexes have also been reported using hydrocarbon matrices at 77 K in conjunction with IR spectroscopy for compounds that cannot be sublimed but are soluble in hydrocarbons …”
Section: Specialist Photochemical Methods For Reactive Intermediates ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the carbonyl bridged structures are thermodynamically favored for both the Fe and Ru systems, but significant contributions from the unbridged (all-terminal) isomers may be present, depending on the medium as well as any substituents on the cyclopentadienyl rings. Whereas all-terminal isomers contribute less than 1% to the solution makeup of Fe 2 Cp 2 (CO) 4 , , the ruthenium analogue Ru 2 Cp 2 (CO) 4 displays more balanced proportions of the bridged and unbridged structures, with as many as three of the four possible isomers being observed by temperature-dependent infrared (IR) spectroscopy. , In contrast, equilibria between bridged and unbridged isomers have not been observed for the osmium analogues. Thus, the Cp complex 1 retains its all-terminal structures, anti - 1 and gauche - 1 , while undergoing an increase in contribution of the more polar gauche isomer in higher polarity solvents .…”
Section: Introductionmentioning
confidence: 99%
“…4 The photochemical reactivity of homoleptic metal carbonyl dimers of Mn, [5][6][7][8] Re, [9][10][11] and Co, 12 have been characterized in detail, as has that of the cyclopentadienyl carbonyl-complexes of Mo, 13,14 W, 15,16 Fe, [17][18][19][20][21] and Ru. [22][23][24][25] Only a limited number of investigations have been made into the photochemistry of tetracarbonyl group VI dimers, [CpM(CO) 2 ] 2 . The structures of these complexes are distinct from those of the other aforementioned metal carbonyl dimers in that the group VI tetracarbonyl dimers are characterized by higher order M-M bonds of bond order three.…”
Section: Introductionmentioning
confidence: 99%